Prediction and surveillance of de novo HCC in patients with compensated advanced chronic liver disease after hepatitis C virus eradication with direct antiviral agents - Elbahrawy, Ashraf; Atalla, Hassan; Mahmoud, Abdulla A.; Eliwa, Ahmed; Alsawak, Alaa; Alboraie, Mohamed; Madian, Ali; Alashker, Ahmed; Mostafa, Sadek; Alwassief, Ahmed; Aly, Hussein H. (Frontiers in Virology, 2023)
The risk of hepatocellular carcinoma (HCC) diminishes in patients with hepatitis C virus (HCV)related advanced chronic liver disease after virological cure. However, despite viral clearance, HCV-induced epigenetic alterations, immune dysregulations, and hepatic parenchymal injuries remain, contributing to de novo HCC occurrence. While HCC incidence is low (0.45 -0.5 %) in patients with advanced fibrosis (F3), the presence of liver cirrhosis and clinically significant portal hypertension increases the HCC risk. The cost-effectiveness of lifelong HCC surveillance in patients with compensated advanced chronic liver disease (cACLD) has sparked debate, raising questions about the most reliable noninvasive tests and stratification models for predicting HCC in patients with sustained virological response (SVR). Furthermore, identifying cACLD patients who may not require long-term HCC surveillance after SVR remains crucial. Several HCC risk stratification scores have been suggested for patients with cACLD, and emerging evidence supports individualized care based on personalized risk assessments. This review focuses on revising the pretreatment and posttreatment predictors of HCC, as well as the indications for HCC surveillance in cACLD patients treated with direct-acting antivirals.